ISOTHERMAL AND NON-ISOTHERMAL TRANSIENT GAS FLOW IN SUBMARINE PIPELINE - Nalin, Augusto F.; Tsukada, Raphael I.; Shiguemoto, Denis A.; Mendes, Jose R. P.; Serapiao, Adriane B. S. [UNESP]; ASME (Amer Soc Mechanical Engineers, 2015)
The discoveries of the Pre-salt oilfields have driven the development of new technologies to enable the production of the deepwater reservoirs. In this scenario, subsea pipelines play an important role. Analysis of the steady and transient flow inside the pipes should be addressed in the design, considering the variation of the fluid properties. In this context, a pipe flow simulator project has been developed to attend gas flow analysis for petroleum industry. In this project, the fluid compressibility factor (Z-factor) and the viscosity are considered function of the pressure, temperature and gas composition. The non-isothermal transient gas flow were calculated using the Method of Characteristics (MOC). The results shown the difference of the isothermal and non-isothermal steady state and transient flow.